Time Factor In Depletion Of Mines - John Roberts (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
THE Federal income tax law permits as a deduction in determining net income "in the case of mines, . . . a reasonable allowance for depletion and for depreciation of improvements, according to the, peculiar conditions in each case, based upon cost, including cost of development not otherwise deducted: Provided, that in the case of such properties acquired prior to Mar. 1, 1913, the fair market value of the property (or the taxpayer's interest therein) on that date shall be taken in lieu of cost up to that date." The law provides for a reasonable allowance but the regulations provide for a definite method of computation that possesses more the virtue of simplicity than that of reasonableness. Article 210 of Regulations 45. reads: "When the cost or value as of Mar. 1, 1913, or within 30 days after the date of discovery of the property shall have been determined, and the number of mineral units in the property as of the date of acquisition or valuation shall have been estimated, the division of the former amount by the latter figure will give the unit value for purposes of depletion, and the depletion allowance for the taxable year may be computed by multiplying such unit value by the number of units of mineral extracted during the year." This is simple, but is it reasonable? The intent of the law is clearly that the cost of the ore in the ground shall be considered as part of the cost of the same ore when removed and sold. The regulations fail to carry out that intent, because of the unwarranted assumption that all the ore in the mine cost the same amount per ton. This is what gives the Treasury Department's method its simplicity, but at the same time robs it of its reasonableness because the assumption is contrary to fact.